Sorghum as a Multifunctional Crop for the Production of Fuel Ethanol: Current Status and Future Trends - Serna-Saldívar, Sergio O.; Chuck-Hernández, Cristina; Pérez-Carrillo, Esther; Heredia-Olea, Erick (IntechOpen, 2012)
None